Stability of micro-periodic materials under finite deformations - Wierzbicki, E.; Woźniak, C.; Woźniak, M. (Archives of Mechanics, 1997)
A new approach to the stability analysis for highly-elastic micro-periodic composite materials subjected to finite deformations is proposed. The analysis is based on the refined macrodynamics of periodic structures which describes the effect of the microstructure size on the dynamic body behaviour. It is shown that the loss of stability can take place both on the macro- and micro-level and that the internal dynamic instability depends on the microstructure size. The obtained results are illustrated by a simple example.